Development and Psychometric Properties of Moral Disengagement Scale for Adolescents - Saima Riaz, Zaqia Bano (Pakistan Journal of Psychology, 2018)
The purpose of the present study was to construct an indigenous tool of Moral Disengagement for Adolescents based on Bandura’s model of moral disengagement. Initially, item pool of 90 items was generated through a review of literature and seeking experts’ opinion. This Item pool was lessened to 76 items after carrying out expert evaluation and pilot testing. Test-retest procedure scrutinized 40 highly correlated items later on. For factor analysis, sample of 400 adolescents with mean age 16.72 years (SD=1.84) was selected. Exploratory Factor Analysis resulted into six factors comprising of 26 items (KMO= .8). Rotated Varimax factor analysis of 26 items showed that factor loadings range from .42 to .79 for the six factors, which explain 52.28% of the total variance. Confirmatory factor analysis confirmed the same structure after deletion of two more items with good model fit indices into six subcategories. Alpha reliability for full scale was .80 indicating that scale is highly reliable. Results of subscale and total scale scores and items and subtotal scores ranges from high to adequate which are indicating the internal consistency of Moral Disengagement Scale for adolescents.